Gambaran Pelaksanaan Pijat Oksitosin pada Ibu Menyusui di RS Siti Khodijah Muhammadiyah Cabang Sepanjang - Umi Marifah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: to see an overview of the implementation of oxytocin massage in breastfeeding mothers at the RS Siti Khodijah Muhammadiyah Cabang Sepanjang Hospital.Methods: The design of this study is quantitative descriptive research. The population in this study was all postpartum mothers in the Siti Khodijah Muhammadiyah Cabang Sepanjang Hospital for three months, amounting to 60. Sample of a million 21 postpartum mothers with purposive sampling techniquesResults: Most respondents in the reproductive age of 20-35 years were 81%, 11 people were multigravida (52%), the majority had a majority sma background of 48%, and most worked with a percentage of 62%. Maternal knowledge of oxytocin massage Is mainly lacking, with a total of 9 respondents, as much as 42%. Respondents’ attitudes about oxytocin massage were primarily positive, as much as 57%. Most postpartum mothers' behaviour toward oxytocin massage was 48% good.Conclusion: Knowledge about oxytocin massage in postpartum mothers at the Siti Khodijah Muhammadiyah Cabang Sepanjang Hospital. In 2019 most have good knowledge of negative attitudes and postpartum mother behaviours about good oxytocin massage.